2019
DOI: 10.1007/s00216-019-02178-2
|View full text |Cite
|
Sign up to set email alerts
|

In vitro determination of diamine oxidase activity in food matrices by an enzymatic assay coupled to UHPLC-FL

Abstract: Intestinal diamine oxidase (DAO) acts as a protective barrier against exogenous histamine. A deficit of DAO activity can lead to the appearance of histamine intolerance, a clinical condition that may be treated by a low-histamine diet and oral DAO supplementation to enhance intestinal histamine degradation. As sources of DAO, porcine kidneys and certain legume seedlings are suitable components for the formulation of a DAO supplement. The aim of this work was to develop a rapid and reliable methodology for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 50 publications
0
17
0
3
Order By: Relevance
“…This technique, based on the radioactive labeling of putrescine and the scintillation counting of its consumption, is advantageous in terms of rapidity and sensitivity, but it was mainly conceived to be applicable to serum samples. Comas-Basté et al have recently developed a rapid and reliable methodology through ultra-high performance liquid chromatography and fluorimetric detection (UHPLC-FL) for the in vitro determination of DAO activity specifically for the analysis of unpurified complex matrixes, such as porcine kidney extract and DAO supplements [ 129 ]. This methodological approach is based in the direct determination of histamine degradation and overcomes certain drawbacks in terms of matrix interferences and handling of radioactive materials.…”
Section: Histamine Intolerancementioning
confidence: 99%
See 4 more Smart Citations
“…This technique, based on the radioactive labeling of putrescine and the scintillation counting of its consumption, is advantageous in terms of rapidity and sensitivity, but it was mainly conceived to be applicable to serum samples. Comas-Basté et al have recently developed a rapid and reliable methodology through ultra-high performance liquid chromatography and fluorimetric detection (UHPLC-FL) for the in vitro determination of DAO activity specifically for the analysis of unpurified complex matrixes, such as porcine kidney extract and DAO supplements [ 129 ]. This methodological approach is based in the direct determination of histamine degradation and overcomes certain drawbacks in terms of matrix interferences and handling of radioactive materials.…”
Section: Histamine Intolerancementioning
confidence: 99%
“…Several studies have demonstrated the capacity of this product to degrade histamine and other biogenic amines in vitro [ 57 , 129 , 130 , 131 , 132 , 133 ]. A wide variability of the DAO capacity of porcine kidney extracts has been reported (with values ranging from 0.1 to more than 100 mU/mg), depending on the purification grade applied to the matrix and/or the amine compound used as the reaction substrate [ 57 , 129 , 130 , 131 , 132 , 133 ]. In fact, many of these works sought the selective purification of the DAO enzyme to design biosensors for the biorecognition of biogenic amines as indicators of freshness in foods [ 134 ].…”
Section: Histamine Intolerancementioning
confidence: 99%
See 3 more Smart Citations